Flow behaviours of cellulose and carboxymethyl cellulose from grapefruit peel - Karatas, Mukaddes; Arslan, Nurhan (Elsevier Sci Ltd, 2016)
The viscosity of cellulose from defatted, protein, pectin and hemicellulose free, delignified grapefruit peel was measured at different temperatures (10-60 degrees C) and concentrations (1-10 kg/m(3)) with a capillary flow technique. The effects of concentration and temperature on the viscosity of cellulose were examined by utilizing sixteen derived models describing the combined effects of temperature and concentration on the viscosity. The constants of models fitted to the experimental data were predicted by nonlinear regression analysis. The grapefruit peel cellulose was converted carboxymethyl cellulose (CMC) by etherification using sodium monochloroacetate and sodium hydroxide. The apparent viscosities of CMC from grapefruit peel cellulose were measured by using a rotational viscometer at concentrations varied from 15 kg/m3 to 35 kg/m3 for temperatures 10-60 degrees C. Apparent viscosity decreased with increasing shear rate. Apparent viscosity increased with an increase in concentrations for all temperatures and decreased with the temperature at which viscosity was measured. The Arrhenius equation was used to describe the temperature dependence of viscosity. The power law, Bingham and Casson models were used for description of flow. The power model given a good fit for the experimental data of CMC at different temperatures and concentrations. The consistency coefficient and flow behaviour index were calculated by using the power-law model. The CMC solutions were found to exhibit pseudoplastic and thixotropic flow behaviours. At various stages of cellulose and CMC production that concentrations and temperatures changed, the best model among derived models may be used to estimate the viscosity of cellulose and CMC from grapefruit peel in the range of temperatures and concentrations studied. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Grapefruit peel; Cellulose; Carboxymethyl cellulose; Flow behaviour